Praktik Pengalihan Pembayaran Dalam Jual Beli Barang Kredit Kepada Pihak Lain Perspektif Hukum Islam - Hasanah, Uswatun; Setiawan, Dedi; Aulia, Nida (Universitas Islam Negeri Raden Intan Lampung, 2022)
The purpose of this study is to discuss diverting payments to other parties in terms of buying and selling credit goods. These cases have recently rampant occurred in the midst of modern society. Therefore, we tried to find out how Islamic law views such practice. The method used in this study is library research, conducted by collecting library materials such as journals, books, and archives of literature documents. We review them with various theories that have a relationship with the problem being investigated. As for sources for primary legal theory in our research, we used the Quran, Hadith, Laws, and Regulations. The result of our study concludes that the practice of diverting payments to other parties in the sale and purchase of credit goods today, in fact, only involves the first and second buyers unbeknownst to the leasing company - which is supposedly the legal owner of the credit goods being traded. Originated from such a problem transaction that ignores the procedural and regulatory aspects of the leasing company, it causes a default in the form of delays in payment of installments and embezzlement credit objects. Even though this is a common issue, however, in the view of Islamic law, diverting payments to other parties in buying and selling credit goods is allowed as long as it meets the requirements and pillars and is based on the correct procedure by involving the leasing party.Keywords: Credit Goods, Islamic Law, Diverting of Payments,